Activity of ceftolozane/tazobactam against clinical isolates of Pseudomonas aeruginosa from patients in the Middle East and Africa – Study for Monitoring Antimicrobial Resistance Trends (SMART) 2017-2020. (December 2022) - Lob, Sibylle H.; Estabrook, Mark A.; DeRyke, C. Andrew; Alekseeva, Irina; Siddiqui, Fakhar; Young, Katherine; Motyl, Mary R.; Sahm, Daniel F.
Highlights: We evaluated the activity of ceftolozane/tazobactam (C/T) against Pseudomonas aeruginosa . C/T was active against 91.4% and 87.0% of isolates from the Middle East and Africa. This activity was higher than that of any of the tested β-lactam comparators. Antimicrobial activity and prevalence of β-lactamases varied across countries. C/T represents an important option in the treatment of infections caused by P. aeruginosa. Abstract: Objectives: We evaluated the activity of ceftolozane/tazobactam (C/T), and comparators against clinical Pseudomonas aeruginosa isolates collected for the global Study for Monitoring Antimicrobial Resistance Trends (SMART) surveillance program in ten countries in the Middle East and Africa to augment scarce standardized surveillance data in this region. Methods: Minimum inhibitory concentrations (MICs) were determined using Clinical and Laboratory Standards Institute broth microdilution and interpreted with European Committee on Antimicrobial Susceptibility Testing breakpoints. P. aeruginosa isolates testing with C/T MIC >4 mg/l or imipenem MIC >2 mg/l were screened for β-lactamase genes. Results: C/T was active against 91.4% and 87.0% of P. aeruginosa isolates from the Middle East and Africa, respectively (14-21 and 7-16 percentage points higher than most β-lactam comparators, respectively). Considerable variation in susceptibility was seen across countries, which largely correlated with the observed prevalence of carbapenemases and/or extended-spectrum β-lactamases. Differences across countries were smaller for C/T than for the β-lactam comparators, ranging from 81% C/T-susceptible among isolates from Jordan to 95% for Qatar. Among subsets resistant to meropenem, ceftazidime, or piperacillin/tazobactam, C/T maintained activity against 51-73% of isolates from the Middle East and against 27-54% from Africa (where metallo-β-lactamase and GES carbapenemase rates were higher). Conclusion: Given the desirability of β-lactam use among clinicians, C/T represents an important option in the treatment of infections caused by P. aeruginosa .